2017
DOI: 10.1007/s00540-017-2354-y
|View full text |Cite
|
Sign up to set email alerts
|

A lateral paracarotid approach for ultrasound-guided stellate ganglion block with a linear probe

Abstract: Recent reports suggest that ultrasound-guided stellate ganglion block (SGB) is safer and more accurate than classic SGB by the using the surface anatomical landmark. However, previous reports concern the classic paratracheal approach using a small specialized curved probe, which may not be appropriate in some patients. The authors have attempted several approaches, including paratracheal, trans-thyroidal, lateral paracarotid, and lateral approaches, to find a safe and suitable method for real-time ultrasound-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…12 Ultrasound guidance could improve the accuracy of local anesthetic injection into target site. 15,16 The use of ultrasound-guided in the index case it apparently helpful in achieving therapeutic action.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Ultrasound guidance could improve the accuracy of local anesthetic injection into target site. 15,16 The use of ultrasound-guided in the index case it apparently helpful in achieving therapeutic action.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, 2-mL 2% lidocaine was injected between the internal carotid artery and the longus colli at the C7 level under ultrasound guidance ( Figure 2). 15,16 The block was repeated once every day, and the pain subsided rapidly in both intensity and frequency along with the advancement of daily treatment. On the seventh day after treatment initiation, the patient no longer had pain episode.…”
Section: Case Presentationmentioning
confidence: 99%
“…Ultrasound-guided SGB has several advantages, including safety, rapid onset of Horner’s sign and lower volumes of local anesthetic, compared with the landmark technique [1,4,17]. Authors have already reported that the lateral paracarotid out-of-plane approach (Song’s technique) for real-time ultrasound-guided SGB at C6 is a safe and suitable method [3,4]. Lee et al reported that a 2mL dose was sufficient for successful SGB when performing ultrasound-guided SGB at C6 [18].…”
Section: Discussionmentioning
confidence: 99%
“…For SGB at C6, a lateral paracarotid out-of-plane approach was performed for ultrasound-guided SGB (Fig. 1) [3,4]. A total of 4mL of 0.2% ropivacaine was injected to achieve blockade.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation